2010
DOI: 10.1039/b923528k
|View full text |Cite
|
Sign up to set email alerts
|

Total synthesis of (±)-aspercyclide A and its C19 methyl ether

Abstract: The total syntheses of (±)-aspercyclide A (1) and its C19 methyl ether derivative (15a) are described. ELISA studies show that both compounds display comparable antagonist activity against the IgE–FcεRI protein–protein interaction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 26 publications
0
27
0
Order By: Relevance
“…Upon reaction with sodium iodide and catalytic amounts of copper(I) iodide and (±)- trans - N , N ′-dimethyl-1,2-cyclohexanediamine in dioxane at 110°C, a variety of aryl bromides 11 Br could be smoothly converted to their iodinated analogs 11 I with excellent yields. The scope of the reaction was shown to be remarkably broad and this process clearly is one of the most efficient to date, as exemplified with representative synthetic application of this process that will be overviewed in section Synthetic Applications of Halogen Exchanges in Aryl Halides and its use in natural product synthesis (Fürstner and Kennedy, 2006 ; Carr et al, 2010 ). It was later on extended to other (hetero)aryl bromides (Lützen et al, 2014 ) and to continuous flow chemistry using a sodium iodide packed-bed reactor (Chen et al, 2014 ) and recent studies demonstrated that the reaction time could be shortened using microwave irradiation (Cannon et al, 2011 ) and that other diamines and some triamines (Jin and Davies, 2017 ) could also be used as ligands.…”
Section: Halogen Exchange In Aryl Halidesmentioning
confidence: 99%
“…Upon reaction with sodium iodide and catalytic amounts of copper(I) iodide and (±)- trans - N , N ′-dimethyl-1,2-cyclohexanediamine in dioxane at 110°C, a variety of aryl bromides 11 Br could be smoothly converted to their iodinated analogs 11 I with excellent yields. The scope of the reaction was shown to be remarkably broad and this process clearly is one of the most efficient to date, as exemplified with representative synthetic application of this process that will be overviewed in section Synthetic Applications of Halogen Exchanges in Aryl Halides and its use in natural product synthesis (Fürstner and Kennedy, 2006 ; Carr et al, 2010 ). It was later on extended to other (hetero)aryl bromides (Lützen et al, 2014 ) and to continuous flow chemistry using a sodium iodide packed-bed reactor (Chen et al, 2014 ) and recent studies demonstrated that the reaction time could be shortened using microwave irradiation (Cannon et al, 2011 ) and that other diamines and some triamines (Jin and Davies, 2017 ) could also be used as ligands.…”
Section: Halogen Exchange In Aryl Halidesmentioning
confidence: 99%
“…In recent years, a wide array of metal-catalyzed coupling reactions has been effectively applied to C-C bond formation, including the C-C bond formation for the construction of macrocycle [7][8][9][10]. We next set out to explore ring-closing strategy via palladium-catalyzed intramolecular C-C bond formation.…”
Section: Evaluation Of Alternative Ring-closing Strategymentioning
confidence: 99%
“…The palladium complexes 10a,b are thermally considerably more stable than palladium complexes with triorganylphosphine ligands. In addition, the Pd 0 -carbene complex 10b has an extremely high activity with long-term stability in the Heck reaction: with only 4 × 10 −4 mol% of catalyst, Pd(OTfa) 2 Coupling of benzoic acids [53] Air stable [54] PdCl 2 Coupling of aryl or vinyl arenecarboxylates [55] Least expensive Pd salt [56a] [Pd(acac) 2 ] Aryl iodides - [45,57] [Pd(dba) 2 ] Aryl and alkenyl halides, benzyl acetates…”
Section: 22 the Catalystsmentioning
confidence: 99%